From the Director: A Reflection on South Africa’s Migration Policy - Carciotto, Sergio (African Human Mobility Review, 2021)
Albeit geographically distant, Europe and South Africa have a great deal of similarities in their management of migratory flows. As many countries in Europe, South Africa is a migration hub attracting numerous migrants, including refugees, seasonal workers, students, cross-border traders and entrepreneurs from both the rest of Africa and Asia. South Africa is also considered, like European states, a country with a generous welfare system, where over 10 million people are living below the poverty threshold and are relying on social grants as a main source of income. Moreover, because of its strong social and economic contradictions, South Africa is not immune to divisive populist politics and xenophobic reactions. Although up to now no nationalist anti-immigration party has emerged in the political arena, immigrant workers (amakwerekwere1) are often accused of stealing jobs and being a burden on the country’s economy. On many occasions, the discontent of poor and disenfranchised black communities has raised tensions and led to violent clashes between locals and foreign nationals.